Analisis Faktor Penyebab Keterlambatan Pengajuan Klaim BPJS Rawat Inap ke Verifikator BPJS di RSUD Genteng Banyuwangi - Novita Nuraini; Puput Puji Lestari (Politeknik Negeri Jember, 2021)
The BPIS claims process for inpatient admissions starts from registration until the patient file is entered into the lINA-CBGs application. Claim submission under the claims verification technique instructions is limited to the 10th of the following month. RSUD Genteng in filing a claim exceeds the 10th of the following month. The purpose f this research is to analyze the factors causing the delay in submitting BPIS claims for hospitalization to BPJS verifier in RSUD Genteng, determining the priority of the problem and the improvement efort to the problem. Type of this research is qualitative using a system approach based on 7M factor (Man, Method, Materials, Machine, Money, Market and Minute). Methods of data collection using observation, interview and documentation. Based on the result of NGT that has been done, the priority of problem causing delay is RM refund more than 2x24 hours, internet network is less stable, less discipline officer, no claim submission SOP, DPJD main diagnosis placement and BPJS verifator of different perception. Improvement eforts that can be done is to make SOP return of medical records of inpatient and SOP related to claims of inpatient BPJS, repair internet network, conduct coordination meeting among officer related to office discipline and make special form for correction from BPJS verifier. Keywords: Delay, Claim BPJS, Inpatiens, Hosppital.